(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
N’-(2-pyridinylmethylene)nicotinohydrazide A, N’-(4-pyridinylmethylene)nicotinohydrazide B, N’-(2- ethoxybenzylidene)nicotinohydrazide C, N’-(4- ethoxybenzyldene)nicotinohydrazide D and N’-(2-hydroxyl-5-methoxybenzylidene)nicotinohydrazide E, was prepared by refluxing the ethanolic solution of nictonic acid hydrazide and ethanolic solutions of 2-pyridinrcarboxaldehyde, 4-pyridinecarboxaldehyde, 2-ethoxybenzaldehyde, 4-ethoxybenzaldehyde and 2-hydroxy-5-methoxybenzaldehyde in 1:1 mole ratio for 4 hours in a separate reactions. The compounds obtained had a melting point between (120-236 oC) and a percentage yield between (52.38-77.70 %). They were crystalline solids. The compounds’ solubility were assessed in water, ethanol, methanol, acetone, hexane, diethyl ether, dimethyl sulfoxide (DMSO), ethyl acetate, and chloroform. The substances were discovered to be fully soluble in DMSO and methanol. FT-IR, 1H-NMR and 13C-NMR were used for the characterization of the compounds. The antibacterial and antifungal properties were tested against Methicillin-resistant Staphylococcus Aureus, Vancomycin-resistant Enterococci, S. aureus, S. typhi, P. aeruginosa, A. nigre, A. flavus, and C. albicans. The zones of inhibitions ranged from 22 to 28 mm and the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) were found to be 0.063 mg/mL, 0.125 mg/mL and 0.125 mg/mL respectively. These indicated that the compounds might be good potential drug candidates.